The Effect of Hexane Fractionation of Plectranthus amboinicus Leaf Extract on the Formation of Fusobacterium nucleatum Inhibition Zone - Anggraeni, Rezky (Journal of Indonesian Dental Association, 2024)
Introduction – Pendahuluan: Periodontitis is an inflammatory disease in the oral cavity commonly experienced by the Indonesian population. In addition to therapeutic periodontal therapy, preventive care is also needed, such as plaque control by brushing teeth and using mouthwash. Plectranthus amboinicus leaves are a plant used by some Indonesian communities as herbal medicine. Plectranthus amboinicus is one of the plants that is known to have antibacterial activity. Objective – Tujuan: To determine the inhibitory activity of hexane fraction extract of P. amboinicus leaves against F. nucleatum bacteria. Methods – Metode: Fusobacterium nucleatum bacteria were treated with hexane fraction extract of P. amboinicus leaves at concentrations of 25%, 50%, and 75% for 24 hours to measure the diameter of the inhibition zone, followed by statistical tests, namely Post Hoc Test to see differences in each treatment group. Results – Hasil: Phytochemical testing results showed that the hexane fraction extract of P. amboinicus leaves contained active compounds such as phenols, steroids, tannins, and alkaloids. Among the three concentrations of hexane fraction used, the 75% concentration exhibited the greatest inhibitory activity against F. nucleatum. Conclusion – Kesimpulan: Hexane fraction extract of P. amboinicus leaves possesses inhibitory activity against F. nucleatum bacteria.